Durkin’s propagation model based on triangular irregular network terrain - Vuckovik, Marija; Trajanov, Dimitar; Filiposka, Sonja (Springer, Berlin, Heidelberg, 2010)
Propagation models that are commonly used in assessing the performances of ad hoc networks, take into account the mechanisms of reflection, diffraction and scattering on the ground. However, it must not be forgotten that the communication between devices is usually carried out in irregular terrain, so it's necessary to use the terrain profile in order to determine the signal coverage. In this paper we layout the extension of the Durkin’s propagation model using Triangular Irregular Network (TIN) based terrain. The verification of the proposed propagation model is done by comparing the results with the ones obtained with a SRTM map used in the Radio Mobile software.
Keywords: TIN Terrain, Durkin’s propagation model, wireless networks